Abdominal injuries in road traffic accidents – an autopsy study - Slović, Živana S.; Vitošević, Katarina; Mihajlović, Filip; Trifunović, Aleksandar; Todorović, Miloš (Vojnosanitetski pregled, 2023)
Background/Aim. Traffic accident injuries are a major public health problem worldwide, with millions of people dying every year. Although the improvement of traffic safety is based on preventive action, it is necessary to conduct an analysis of victims in traffic in order to prevent future traffic accidents with the help of such findings. The aim of the study was to determine the manner of occurrence of abdominal injuries (AIs), gender differences, and the sitting position in the vehicle that affects the severity of AIs, as well as which AIs lead more often to fatalities in traffic accidents. Methods. Materials for the present study were collected from the medico-legal autopsies, showing AIs that occurred in road traffic accidents. The total number of people who died from sustained injuries or complications of the injuries after road traffic accidents was 525. Results. In the study sample, 38.3% of subjects sustained abdominal trauma. Men were more likely to have AIs, and passengers in the front seat and motorcycle drivers were identified as the most vulnerable category of these types of injuries. The liver was the most commonly injured abdominal organ. Liver destructions, liver lacerations, spleen lacerations, intestinal injuries, the simultaneous occurrence of head, chest, and AIs, or the simultaneous occurrence of head and AIs in a higher percentage led to death at the scene. Conclusion. The results of this study represent the basis for creating educational content for all traffic participants as well as the legislation in the field of traffic safety.
Keywords: abdominal injuries; accidents, traffic; autopsy; cause of death; risk assessment; sex factors